Hubungan Pola Asuh Orangtua dengan Motivasi Belajar Remaja - Cindy Marisa; Evi Fitriyanti; Sri Utami (Jurnal Konseling dan Pendidikan, 2018)
This research is based on parents' thinking is an important learning motivator for children, including in adolescence, because the family is the first and main environment. Provision of appropriate parenting patterns should also follow a good child's learning motivation. This study aims to determine whether there is a significant positive relationship between the pattern of care with motivation in learning, and knowing where old parenting patterns have the motivation to learn. The research design used herein is correlative with the method. Data taken by using closed questionnaires. Data were analyzed using Spearman's rho test. With this method researchers collect as much data as possible about the dimensions of motivation to learn, then do the analysis of these dimensions to get the complete data and as objective as possible with the pattern of care and motivation to learn adolescents. Testing is done by t test. Based on the data analysis can be concluded there is a significant relationship between the pattern of care with adolescent learning motivation with a contribution of 18.8%, where again increased adolescent learning motivation caused by other factors.